A review of photonic crystal fiber sensor applications for different physical quantities. Issue 6 (3rd July 2018) - Zhang, Tianyu; Zheng, Yu; Wang, Chengming; Mu, Zhengming; Liu, Yujuan; Lin, Jun
ABSTRACT: Since the early conceptual and practical demonstrations in the late 1990s, photonic crystal fibers (PCFs) have attracted considerable interest by virtue of their promise to deliver a unique range of optical properties that are simply not possible in standard fiber types. Hollow-core photonic band gap fiber has the potential to overcome some of the fundamental limitations of solid fiber as they also provide a unique medium for a range of light. PCF also be used as a unique optical material to make sensors due to the air-holes that can be filled with different materials (liquid, gas or even solid) to alter the difference of refractive index (RI) in the two modes, has been used in various sensing search fields. The application of PCF on physical quantities is discussed, and the recent results on temperature, magnetic, strain and vibration are reviewed. These developments demonstrate that the enlarged complexity and decreased accuracy of sensors offered by PCF make it useful in a wide range of engineering monitoring applications.